Awareness of Hepatitis B Infection Amongst the People of Southeastern Anatolia: A Seroprevalence Study - Metin Çalışır (Cumhuriyet University, 2018)
Objective: Viral hepatitis has become a silent epidemic worldwide. The aim of the present study is to determine the knowledge and awareness of Hepatitis B infection amongst patients who refer to our clinic and their relatives. Material-Method: 244 patients randomly selected from among patients admitted to our clinic were included this study and data about Hepatitis were obtained. Then, hepatitis condition of the patients was determined by The enzyme-linked immunosorbent assay (ELISA). The data were compared. Results: 72 patients were Antibody to the hepatitis B surface antigen(+) (anti-HBs (+)). 25 patients had received three doses of the hepatitis B vaccine and 47 patients were unaware of their anti-HBs (+) status. 14 patients were Hepatitis B surface antigen(+) (HBsAg (+)). 11 patients had known HBsAg (+) and 3 patients were unaware of their condition. Conclusions: In order to decrease the burden of hepatitis in dental health care workers, it is recommended that the dental professionals should receive immunization against hepatitis virus and should use individual protective equipment such as gloves, head caps, masks, etc. Necessary tests for the infectious diseases should be applied to all patients admitted to the clinic.